The Importance of Shrines in The Spiritual Life and Mentality of Uzbek People - Abdurakhmanova, Jumagul Namozovna; Jumaeva, Shoira Berdiyarovna; Ismailov, Ulugbek Kuchkarovich (International Journal of Psychosocial Rehabilitation, 2020)
This article focuses on the issue of shrines and pilgrimage ceremonies as one of the most topical issues today and analyzes the history of the study of shrines and holy places in Uzbekistan, as well as the rituals of pilgrimage.